Legal Review of Islamic State Administration on the Performance of State Civil Apparatus in Public Health Service According to Law Number 25 of 2009 (Case Study: Putri Hijau Hospital) - Rahmah, Siti; Lubis, Syofiaty (UNIVERSITAS PAKUAN, 2022)
The aim of this research is to explore the concept of Islamic Constitutional Law in public healthcare services, examining Law Number 25 of 2009 regarding public services in relation to public healthcare, as well as reviewing the application of Islamic Constitutional Law to the performance of civil servants in providing public healthcare services according to Law Number 25 of 2009, specifically focusing on the case of Putri Hijau Hospital. The research methodology employed in this study is library research, utilizing a statutory approach to examine how Islamic Constitutional Law views the performance of civil servants in delivering public healthcare services based on the provisions of Law Number 25 of 2009 (a case study of Putri Hijau Hospital). Based on the research findings, it was observed that the performance of civil servants in providing healthcare services has been diligently pursued to the best of their abilities, yet it remains imperfect and incomplete. Furthermore, with regard to Law Number 25 of 2009 on Public Services in Putri Hijau Hospital, it was found that the hospital has implemented the provisions outlined in the law, although there are still members of the public who express dissatisfaction with the quality of the services provided.